Pengaruh Kualitas Pelayanan Dan Harga Terhadap Loyalitas Pelanggan (Studi Pada Konsumen Lapangan 916 Futsal) - Ahmad Munif; Agus Widarko; M. Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to determine and analyze Service Quality and Prices on Customer Loyalty in 916 Futsal Field Consumers, either partially or simultaneously. This researcher uses an explanatory research type with a quantitative approach. The population in this study were consumers in the 916 field. Samples were taken as many as 74 respondents. The sampling technique used was the Yamane approach. Data were analyzed using multiple linear analysis processed with SPSS 2020 software. The data collection method used was a questionnaire. The results showed that service quality partially significant effect on customer loyalty. Meanwhile, price has an effect, but not partially significant, on customer loyalty. And, service quality and price have a significant effect simultaneously on purchasing decisions. Keywors: Service Qualty, Price and Loyalty